SEARCHING FOR A SAFE PLACE ON THE EARTH. EUROPE IN SELECTED STATISTICS OF NATURAL DISASTERS IN 21ST CENTURY - Matera, Rafal; Kowalski, Kamil (European Scientific Journal, ESJ, 2014)
The article discusses the issue of placing Europe in various international statistical analyses of natural disasters in the 21st century. The analysis includes the subject of the relative safety (or danger) of inhabiting this region (compared with other continents) of the world for the occurrence of natural disasters. According to a variety of statistical sources for the researched period the Old Continent seemed a relatively safe area, free of the most destructive disasters. This was reflected in the relatively low percentages of human losses and material ones in Europe. The study benefits by a number of sources, but mainly was based on â€œAnnual Disaster Statistical Review. The Number and Trendsâ€ published by the Centre for Research on the Epidemiology of Disasters in Brussels.